The Ending of Mad Men's Fifth Season: Cinema, Serial Television and Moments of Performance. Issue 3 (1st January 2014) - Logan, Elliott
Abstract: Certain television dramas of the past thirty years have often been described as 'cinematic' for displaying stylistic tendencies historically associated with feature films. This article argues that describing such shows as 'cinematic' misrepresents movies and television serials as artistic mediums, and tends to obscure their distinctive achievements. Against this critical tendency, the article accounts for the ending of Mad Men's fifth season not in terms of the series' 'cinematic' style, but in terms of how it handles images of faces and places to carry and express the special burden of history and future available to long-form serial television.